The Genetic Dissection of Ace2 Expression Variation in the Heart of Murine Genetic Reference Population - Xu, Fuyi; Gao, Jun; Munkhsaikhan, Undral; Li, Ning; Gu, Qingqing; Pierre, Joseph F.; Starlard-Davenport, Athena; Towbin, Jeffrey A.; Cui, Yan; Purevjav, Enkhsaikhan; Lu, Lu (Frontiers in Cardiovascular Medicine, 2020)
Background: High inflammatory and cytokine burden that induces vascular inflammation, myocarditis, cardiac arrhythmias, and myocardial injury are associated with lethal outcome in COVID-2019. SARS-CoV-2 virus utilizes the ACE2 receptor for cell entry similar to SARS-CoV. This study investigated the regulation, gene network and associated pathways of ACE2 that may be involved in inflammatory and cardiovascular complications of COVID-19. Methods: Cardiovascular traits were determined in the currently largest mouse genetic reference population -- BXD recombinant inbred strains using blood pressure (BP), electrocardiography (ECG) and echocardiography measurements. Expression quantitative trait locus (eQTL) mapping, genetic correlation, and functional enrichment analysis were used to identify Ace2 regulation, gene pathway and co-expression networks. Results: A wide range of variation was found in expression of Ace2 among the BXD strains. Levels of Ace2 expression is negatively correlated with cardiovascular traits including systolic and diastolic blood pressure, P wave duration and amplitude. Ace2 co-expressed genes are significantly involved in cardiac and inflammatory related pathways. The eQTL mapping revealed Cyld is a candidate upstream regulator for Ace2. Moreover, the protein-protein interaction network analysis inferred several potential key regulators (Cul3, Atf2, Vcp, Jun, Ppp1cc, Npm1, Mapk8, Set, Dlg1, Mapk14, and Hspa1b) for Ace2 co-expressed genes in heart. Conclusions: Ace2 is associated with blood pressure, atrial morphology and sinoatrial conduction in BXD mice. Ace2 co-varies with Atf2, Cyld, Jun, Mapk8, and Mapk14 and enriched in RAS, TGFβ, TNFα, and p38α signaling pathways, involved in inflammation and cardiac damage. We suggest that all these novel ACE2-associated genes and pathways may be targeted for preventive, diagnostic, and therapeutic purposes in cardiovascular damage in patients with systemic inflammation, including COVID-19 patients.